Divergence Between Sympatric Rice- and Soybean-Infecting Populations of Rhizoctonia solani Anastomosis Group-1 IA - de Assis, Joana Bernardes; Peyer, Patrik; Rush, Milton C.; Zala, Marcello; McDonald, Bruce A.; Ceresini, Paulo C. [UNESP] (Amer Phytopathological Soc, 2008)
Rhizoctonia solani anastomosis group (AG)-1 IA causes soybean foliar blighting (aerial blight) and rice sheath blight diseases. Although taxonomically related within the AG-1 complex, sister populations of R. solani AG-1 IA infecting Poaceae (rice) and Fabaceae (soybean) are genetically distinct based on internal transcribed spacer rDNA. However, there is Currently no information available regarding the extent of genetic differentiation and host specialization between rice- and soybean-infecting populations of R. solani AG-1 IA. We used 10 microsatellite loci to compare sympatric R. solani AG-1 IA populations infecting rice and soybeans in Louisiana and one allopatric rice-infecting population from Texas. None of the 154 multilocus genotypes found among the 223 isolates were shared among the three populations. Partitioning of genetic diversity showed significant differentiation among sympatric populations from different host Species (Phi(ST) = 0.39 to 0.41). Historical migration patterns between sympatric rice- and soybean-infecting populations from Louisiana were asymmetrical. Rice- and soybean-derived isolates of R. solani AG-1 IA were able to infect both rice and soybean, but were significantly more aggressive on their host of on-in, consistent with host specialization. The soybean-infecting Population from Louisiana was more clonal than the sympatric rice-infecting population. Most of the loci in the soybean-infecting populations were Out of Hardy-Weinberg equilibrium (HWE.), but the sympatric rice-infecting population from Louisiana was mainly in HWE. All populations presented evidence for a mixed reproductive system.
Keywords: pathogen emergence; soybean aerial blight